Coating Ti6Al4V implants with nanocrystalline diamond functionalized with BMP-7 promotes extracellular matrix mineralization in vitro and faster osseointegration in vivo - Nemcakova, Ivana; Litvinec, Andrej; Mandys, Vaclav; Potocky, Stepan; Plencner, Martin; Doubkova, Martina; Nanka, Ondrej; Olejnickova, Veronika; Sankova, Barbora; Bartos, Martin; Ukraintsev, Egor; Babčenko, Oleg; et al. (Scientific reports, 2022)
The present study investigates the effect of an oxidized nanocrystalline diamond (O-NCD) coating functionalized with bone morphogenetic protein 7 (BMP-7) on human osteoblast maturation and extracellular matrix mineralization in vitro and on new bone formation in vivo. The chemical structure and the morphology of the NCD coating and the adhesion, thickness and morphology of the superimposed BMP-7 layer have also been assessed. The material analysis proved synthesis of a conformal diamond coating with a fine nanostructured morphology on the Ti6Al4V samples. The homogeneous nanostructured layer of BMP-7 on the NCD coating created by a physisorption method was confirmed by AFM. The osteogenic maturation of hFOB 1.19 cells in vitro was only slightly enhanced by the O-NCD coating alone without any increase in the mineralization of the matrix. Functionalization of the coating with BMP-7 resulted in more pronounced cell osteogenic maturation and increased extracellular matrix mineralization. Similar results were obtained in vivo from micro-CT and histological analyses of rabbit distal femurs with screws implanted for 4 or 12 weeks. While the O-NCD-coated implants alone promoted greater thickness of newly-formed bone in direct contact with the implant surface than the bare material, a further increase was induced by BMP-7. It can be therefore concluded that O-NCD coating functionalized with BMP-7 is a promising surface modification of metallic bone implants in order to improve their osseointegration.
Keywords: Coated Materials, Biocompatible; Extracellular Matrix; Rabbits; diamant; osteointegrace; Titanium; králíci; Animals; Osseointegration; slitiny; extracelulární matrix; Alloys; Bone Morphogenetic Protein 7; Diamond; zvířata; biokompatibilní potahované materiály; kostní morfogenetický protein 7; titan